At the Palaces of Knossos: the disguise of an ambivalence of Nikos Kazantzakis - Μητροφάνης, Γιάννης (Ariadne, 2020)
DURING the years of German occupation of Greece, Nikos Kazantzakis had his most creative writing career. Among other texts that the author worked during that period, Kazantzakis completed the last (?) writing of his novel for children At the Palaces of Knossos, a text which is a cross-section. With this mythological novel, Kazantzakis redefines his relationship with Hellenism and its history. The Minoan Crete is a “mirror image” of British Empire of his time, whereby the narrator exploits the multiperspectivity of the ancient myth and makes a dialogue with travelogues, Odyssey, but mainly with colonial reception of the Minoan archaeology. The comparative approach of the subject, in conjunction with the study of the manuscript At the Palaces of Knossos demonstrates that this text is the prelude of the author’s reconciliation with Hellenism which was validated by his last work Report to Greco (Anafora ston Greco).